Legal Protection For Consumers Buying And Selling Electronic Goods With Defective Products - Arief, Ediyanto; Nurdin, Boy; Budianto, Azis (CV. Publikasi Indonesia, 2023)
Abstract. The presence of Regulation Number 8 of 1999 concerning Purchaser Insurance has concentrated a little since this Regulation controls the privileges and commitments of business entertainers and customers so they are safer and are supposed to turn into a legitimate umbrella for shoppers. Consumers need to know that they have the right to get protection when dealing with sellers or producers in conducting trade transactions so that when a loss occurs on the part of the consumer caused by the seller or producer, the consumer can demand that the seller or producer be responsible for the loss suffered by the consumer. The relationship between sellers as business actors to consumers must be maintained properly. The seller also knows whether there is anything to consider before being marketed or sent to consumers regarding the feasibility of the goods. The eligibility in question is the condition of the goods by the information submitted by the seller, according to what is in the advertisement, the seller has ethics when trading his goods. At the point when a misfortune is capable by the shopper, on the off chance that the proof states whether there was a component of mistake, it stays the obligation of the merchant, as expressed in Article 28 of Regulation Number 8 of 1999 concerning Customer Security.